Correlation between clinical trial endpoints of marketed cancer drugs and reimbursement decisions in China - Kexin Ling; Huli Qin; Yiman Feng; Hongxi Che; Jinxi Ding; Jinxi Ding; Wei Li; Wei Li (Frontiers Media S.A., 2022)
ObjectiveThis study aimed to assess whether different clinical trial endpoints in pivotal trials of cancer drugs were associated with reimbursement decisions in China.Materials and methodsCancer drugs marketed before June 30th, 2021 with publicly available technical review reports for application of drug registration on Center for Drug Evaluation (CDE) website were reviewed. The trial design characteristics and relevant clinical outcomes [e.g., overall survival (OS), progression-free survival (PFS) and objective response rate (ORR)] were extracted from the technical review reports, while the reimbursement decisions were reviewed from National Healthcare Security Administration (NHSA) website. The differences in trial characteristics and clinical outcomes between drugs with positive reimbursement decisions and negative ones were compared by hypothesis test (Pearson's chi-squared test, Fisher's exact test, independent samples t-test and Mann-Whitney U test). The correlation between different clinical trial endpoints and reimbursement decisions was analyzed by multivariate logistic regression.ResultsThere were 112 cancer drug indications included in this study. Among these indications, 76 received a positive reimbursement decision, and the most common primary endpoints of them were PFS (42.1%) and ORR (30.3%). Taking PFS (OR = 7.333) and ORR (OR = 5.271) as the primary endpoints were more likely to receive a positive reimbursement decision compared with OS (P = 0.003). The proportion of drugs marketed with phase I (75.0%) and phase II (85.7%) clinical trials receiving positive reimbursement decisions are significantly higher than those marketed with phase III clinical trials (61.3%, P = 0.043). The magnitude of clinical benefit only had subtle influences (Prisk benefit − OS = 0.627, Prisk benefit − PFS = 0.087, Psurvival benefit − OS = 0.545, Psurvival benefit − PFS = 0.189) on the drug reimbursement decisions, however, the drug prices and clinical needs also made a difference on that.ConclusionThis study found that, in Chinese drug price negotiations from 2017 to 2021, policymakers have focused more on meeting clinical needs and filling therapeutical gaps in National Reimbursement Drug List (NRDL), while requirements for the selection of primary endpoints, clinical trial phases, and clinical benefits have been reduced. In the future, emphasis should be put on the use of surrogate endpoints and clinical benefits.